Pengaruh Durasi Penjemuran Terhadap Kualitas Gabah Padi pada Proses Pengeringan - Anisya Janu Kurnia Mita; Rahmatiyah Rahmatiyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Rice holds a significant place as a staple food in Indonesia, with its life cycle spanning between 3 to 6 months, depending on the specific variety. An essential part of preserving the quality of rice grains is the drying process. This research aims to investigate how drying affects the quality of rice during this crucial stage. The findings of this study are not only intended to build upon previous research but also to serve as valuable guidance for farmers in making informed decisions about the drying process, ultimately ensuring optimal quality in their harvested grains. This study employed an experimental approach using a completely randomized design, wherein treatments were assigned randomly across all experimental units. The results indicated that the duration of drying significantly impacts the quality of rice grains. It was found that optimal drying occurs over a period of 3 to 4 days under sunlight on a tarpaulin base, which can be effectively used as a benchmark for assessing the quality characteristics of milled upland rice.